2004
DOI: 10.1111/j.1365-2133.2004.05986.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of once-daily treatment regimens with calcipotriol/betamethasone dipropionate ointment and calcipotriol ointment in psoriasis vulgaris

Abstract: Two different short-term treatment regimens employing a recently developed two-compound product (calcipotriol/betamethasone dipropionate) provided rapid and marked clinical efficacy and were shown to be safe therapies for psoriasis vulgaris.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
110
3
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(122 citation statements)
references
References 16 publications
8
110
3
1
Order By: Relevance
“…In our study population, the results obtained after the initial phase with Dovobet" could be maintained or further improved with treatment with Daivonex" alone, as shown by previous studies (7,9).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In our study population, the results obtained after the initial phase with Dovobet" could be maintained or further improved with treatment with Daivonex" alone, as shown by previous studies (7,9).…”
Section: Discussionsupporting
confidence: 65%
“…Clinical studies have shown that the combination product has greater efficacy and tolerability and a faster speed of onset than either agent used alone (5)(6)(7)(8)(9)(10). It is usually administered once daily for up 4 weeks followed by maintenance treatments with steroid-free conventional products (e.g., calcipotriol alone).…”
mentioning
confidence: 99%
“…Although calcitriol and calcipotriol (a synthetic VDR ligand) have been approved as topical agents for the treatment of mild to moderate psoriasis, their use (especially oral) has at least in some cases been associated with an increased incidence of hypercalcemia/ hypercalciuria (10)(11)(12)(13)(14), and they exhibit poor efficacy when compared with biologics (15). In the clinic, the therapeutic efficacy of calcitriol and calcipotriol is increased by their use in combination with topical steroids (16,17). Therefore, there is an unmet clinical need for the identification of a new generation of VDR ligands that exhibit an improved therapeutic index (TI).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] The two-compound ointment appears to have an improved tolerability profile vs. either compound alone; this may be due to the vitamin D analogue and steroid components each neutralizing the side-effects of the other agent (e.g. atrophy and tachyphylaxis ⁄ rebound effect may be reduced by the presence of the vitamin D analogue, and irritation may be reduced by the presence of the steroid).…”
Section: Combination Therapy Provides Enhanced Efficacymentioning
confidence: 99%